Poesia swahili in Katanga: multilinguismo e corporalità nei versi di Patrick Mudekereza - Flavia Aiello; Roberto Gaudioso (Kervan. International Journal of Afro-Asiatic Studies, 2019)
The world of Swahili contemporary poetry, as remarked by M. M. Mulokozi and T. S. Y. Sengo (1995: 22), is amazingly broad, given the progressive diffusion of the Swahili language in the course of the last two centuries, from the East African coast to the continental regions of Eastern and Central Africa. Accordingly, authors of Swahili poetic texts can also be found in the “periphery” of the Swahilophone area, such as the Democratic Republic of Congo, where this language has become the medium of modern songs and written poetry in many areas, although the latter is hardly visible in a context where creative writing is predominantly expressed in French. In the present contribution, after an introduction on Swahili poetry in the DRC and on the linguistic complexity of the Swahilophone environment of Katanga, and particularly of its main city, Lubumbashi, we will present some (so far unpublished) poems by Patrick Mudekereza, art curator and director of the cultural centre WAZA, together with a first analysis of his verses, whose poetics emerges from plurilingualism and corporality.